2021
DOI: 10.1038/s41598-021-00583-1
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional analysis of somatic coding and UTR indels in breast and lung cancer genomes

Abstract: Insertions and deletions (Indels) represent one of the major variation types in the human genome and have been implicated in diseases including cancer. To study the features of somatic indels in different cancer genomes, we investigated the indels from two large samples of cancer types: invasive breast carcinoma (BRCA) and lung adenocarcinoma (LUAD). Besides mapping somatic indels in both coding and untranslated regions (UTRs) from the cancer whole exome sequences, we investigated the overlap between these ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…Frameshift INDELs are generally deleterious and contribute to disease susceptibility, as evidenced by human genomics research that has identified many INDELs related to genetic diseases including cancer [ 25 ]. Notably, 29 INDELs detected in exons of 23 genes had Alt alleles causing frameshifts in the 101 horses, indicating that all genotypes were frameshifted in the population.…”
Section: Discussionmentioning
confidence: 99%
“…Frameshift INDELs are generally deleterious and contribute to disease susceptibility, as evidenced by human genomics research that has identified many INDELs related to genetic diseases including cancer [ 25 ]. Notably, 29 INDELs detected in exons of 23 genes had Alt alleles causing frameshifts in the 101 horses, indicating that all genotypes were frameshifted in the population.…”
Section: Discussionmentioning
confidence: 99%
“…Second, evolutionary and population genetic studies have suggested that indels are relatively deleterious if they are long ( Pascarella and Argos 1992 ; Taylor et al 2004 ; Tao et al 2007 ; Hsing and Cherkasov 2008 ; Kim and Guo 2010 ; Mills et al 2011 ; Rockah-Shmuel et al 2013 ; Lek et al 2016 ; Zhang et al 2018 ), cause frameshifts ( Iengar 2012 ; Montgomery et al 2013 ; Chong et al 2013 ; Bermejo-Das-Neves et al 2014 ; Chen and Guo 2021 ), occur internally in the protein ( Lin et al 2017 ), alter flanking amino acids ( Zhang et al 2011 ), or fall outside of disordered regions ( Taylor et al 2004 ; Light, Sagit, Ekman, et al 2013 ; Light, Sagit, Sachenkova, et al 2013 ; Bermejo-Das-Neves et al 2014 ; Khan et al 2015 ). Protein families with indels tend to diverge in their structure and function relative to protein families without indels ( Salari et al 2008 ; Hormozdiari et al 2009 ; Zhang et al 2010 , 2018 ; Gavrilov et al 2015 , 2018 ; Banerjee et al 2019 ; Jayaraman et al 2022 ), suggesting indels can be an important source of evolutionary novelty.…”
Section: Introductionmentioning
confidence: 99%